strategy to increase the number of foreign tourist in Bandung - Tiko Rhamdani S, Raden; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2016)
Abstract - Bandung as one of numerous city destinations of tourism in Indonesia has a lot of history within. In the colonial era, Bandung was used by Dutch Royal to rest and relax. Nowadays, all matters of tourism activities in Bandung are managed by Department of Culture and Tourism Bandung. Since year 2011 until 2014 the growth of foreign tourist in Bandung is getting slower. In the other side, Tourism Minister of Republic Indonesia (Mr. Arief Yahya) set a new target for Department of Culture and Tourism Bandung that the number of foreign tourist must increase to 500,000. Based on that problem, Department of Culture and Tourism Bandung have to figure out the cause of the slowing foreign tourist growth in Bandung and find out the strategy that can be done to achieve target of 500,000 foreign tourist. To solve the problem, this study is using the qualitative methodology with literature and in depth interview approach. The findings on the business issue exploration produce a SWOT (Strength, Weakness, Opportunity, Threat) of Bandung which came from external and internal environment analysis. The issues appeared in external environment, internal environment, and SWOT analysis used by researcher to help find out what is the cause of the slowing foreign tourist growth in Bandung. By using 5 whys method, found that the root cause of the slowing foreign tourist growth is because of lack of public awareness, lack of communication with foreign tourist, inadequate funds, lack of catching the opportunity, and Department of Culture and Tourism Bandung did not do CRM well. The three scenario of the alternatives solution that fit with root cause and used to achieve the number of 500,000 foreign tourist are; Improvement in cleanliness that involve public awareness, Improvement in cleanliness that involves public awareness and multiplies the events in Bandung, Synergize two previous scenario with international events outside Bandung.Â Keywords: Bandung, Tourism, Strategy, Marketing